The Perception of Senior High School Students Toward Their Speaking Anxiety During English Classes: A Narrative Study - Muhamad Zais (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This thesis explores senior high school students’ perceptions of their speaking anxiety during English classes. Using a qualitative research design, the study employs narrative inquiry to gain insights into the psychological, emotional, and social dimensions of speaking anxiety. The research focuses on three students from an accredited state senior high school in Jember, selected through purposive sampling. The participants were interviewed in Bahasa Indonesia to facilitate natural and in-depth responses. The findings reveal that speaking anxiety is a multifaceted phenomenon, influenced by factors such as fear of negative evaluation, limited vocabulary, low self-confidence, and previous negative experiences. Students experienced physiological symptoms like nervousness, sweating, and mental blocks that impeded their ability to speak confidently. The study also highlights the significant role of the classroom environment and teacher behavior in either exacerbating or alleviating students’ anxiety. Teachers who foster a warm and non-judgmental atmosphere help students feel psychologically safe, promoting better participation and improved speaking performance. This research emphasizes the importance of addressing students' emotional and psychological needs in language learning, particularly in speaking activities. The study contributes to existing literature by focusing on high school students’ perceptions of speaking anxiety, an area that has been less explored in previous studies. The findings offer valuable insights for English language educators, helping them create supportive classroom environments and more effective teaching strategies to reduce speaking anxiety.
Reupload file repositori 27 Mar 2026_Maya
Keywords: Speaking Anxiety